2017
DOI: 10.1152/japplphysiol.00132.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mild aerobic exercise blocks elastin fiber fragmentation and aortic dilatation in a mouse model of Marfan syndrome associated aortic aneurysm

Abstract: Regular low-impact physical activity is generally allowed in patients with Marfan syndrome, a connective tissue disorder caused by heterozygous mutations in the fibrillin-1 gene. However, being above average in height encourages young adults with this syndrome to engage in high-intensity contact sports, which unfortunately increases the risk for aortic aneurysm and rupture, the leading cause of death in Marfan syndrome. In this study, we investigated the effects of voluntary (cage-wheel) or forced (treadmill) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 28 publications
2
64
2
Order By: Relevance
“…To date, few studies have reported the safety and effectiveness of exercise in patients with AAA. In a recent report on an exercise program in a mouse model of Marfan syndrome, mild aerobic exercise blocks elastin fiber fragmentation and aortic dilatation . Two pilot studies in 2009 and 2010 reported on the safety and tolerance of exercise in a few patients with AAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few studies have reported the safety and effectiveness of exercise in patients with AAA. In a recent report on an exercise program in a mouse model of Marfan syndrome, mild aerobic exercise blocks elastin fiber fragmentation and aortic dilatation . Two pilot studies in 2009 and 2010 reported on the safety and tolerance of exercise in a few patients with AAA.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report on an exercise program in a mouse model of Marfan syndrome, mild aerobic exercise blocks elastin fiber fragmentation and aortic dilatation. 21 Two pilot studies in 2009 8 and 2010 22 reported on the safety and tolerance of exercise in a few patients with AAA. From the 12-week supervised program of moderate-intensity endurance exercise for patients (n=11) with small AAAs, no increases in AAA size nor any other adverse clinical events were observed at 12 weeks, 23 but there were no follow-up data on patients' clinical outcomes after the exercise program.…”
Section: Discussionmentioning
confidence: 99%
“…29,50,51 Hence, prophylactic treatment of MFS aortic root disease may benefit from endothelial A B functioneoptimized approaches, a claim also supported by the protective effect of mild aerobic exercise on MFS aortic root disease. 52 Although exercise also reduces resting HR, the effect of ATR1a deletion on C1039G mice HR did not reduce aortic root remodeling, further supporting the role of endothelial NO in MFS. Hence, exercise and other welloptimized endothelial functioneenhancing approaches may prove superior to commonly used therapies, a controversial topic in a recent large-scale trial.…”
Section: Discussionmentioning
confidence: 86%
“…A total of 226 studies were found in the main search, 6 of which were selected for this review. One study was selected through review of reference lists, and 1 was included after first review of the article resulting in a total of 8 studies 9,18‐24 . Of the selected studies, 1 was an observational pilot study, 22 2 were case reports, 23,24 and 5 were case‐control studies 9,18‐21 .…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, their results indicated that moderate dynamic exercise mitigates a progression of cardiovascular deficits in MFS mice. Another case‐control study by Gibson et al 19 (2017) studied ~ 60 mice, divided into control groups of 6 to 16 mice and MFS groups of 6 to 16 mice. Both the control groups and the MFS groups were subjected to 6 different regimes, forced exercise at 55%, 65%, 75%, and 85% of VO 2 max, voluntary exercise and a sedentary regime, respectively.…”
Section: Resultsmentioning
confidence: 99%